The Turkic Cultural World of Russia: Loci, Problems, and Research Prospects - Lamazhaa, Chimiza K. (The New Research of Tuva, 2025)
This article analyzes the characteristics and challenges of studying the Turkic cultural world of Russia in contemporary Russian scholarship. The Turkic cultural world is more than just related languages; it is a space of multiple cultures sharing common foundations: origins of history, mythology, folklore, literary traditions, ethnic self-awareness, and a range of cultural customs. The Turkic cultural world of Russia represents a localized part of this broader space.It itself consists of loci of different cultural worlds, which becomes evident when applying methods of cultural geography. This is a linguistic cultural landscape of the spread of the Turkic language group within the Altaic language family. A distinctive feature of Russian Turkic peoples is Turkic-Russian bilingualism. A common characteristic of their sociocultural life can be described historically as a shared history. In religious terms, the Turkic cultural world of Russia includes loci of the Islamic world, Buddhist and shamanistic traditions, as well as Christian-Orthodox elements. There are also a few significant differences. At the same time, the contemporary mosaic Turkic culture demonstrates the presence within its culture of a “core”, i. e., a deep internal layer that has a relatively stable character.However, certain conditions and scientific capabilities are necessary for its study. The article outlines issues facing Russian scholarship in this regard: asymmetry, challenges of planning and financing, problems encountered by regional insider scholars.Cross-cutting thematic approaches are proposed to optimize research strategies. Among these, it is suggested to use the methodology of ethnocultural conceptualization to discuss cultural concepts from the “core” of each culture that are common among Turkic peoples.
Keywords: Turkic language; Turkic culture; cultural world; Turkic peoples; Turkic peoples of Russia; Russian science; asymmetry; cultural core; concept of culture